Corporate Tax Policy: A Comparative Analysis of Corporate Audit Quality - Hendro Paulus; Deden Tarmidi; Shinta Melzatia; Taufik Akbar (IAPI, 2026)
This study aims to analyze the effect of transfer pricing, firm size, and earnings management on tax avoidance, and how audit quality classifies the relationship. The study was conducted on 380 company data by comparing between companies audited by Big Four and non-Big Four Public Accounting Firms (KAP). The regression analysis results show that overall (Model 1), transfer pricing has a significant positive effect on tax avoidance, while firm size has a significant negative effect, and earnings management has no significant effect. In companies audited by Big Four KAP (Model 2), transfer pricing and earnings management show significant influence on tax avoidance, with positive and negative directions respectively. Firm size also shows a significant negative effect in this model. In contrast, for non-Big Four firms (Model 3), only transfer pricing and earnings management have a significant effect on tax avoidance, while firm size has no effect. These results indicate that audit quality plays a role in classifying the effect of firm size and earnings management on tax avoidance. These findings make an important contribution to understanding the dynamics of corporate tax policy and its implications for tax governance and regulation.